The Impact of Virtual Reality Technology on Spatial Intelligence Development in Elementary School Students_VOL 2. No1 - Rahmat Yasin (Innovative Pedagogy and Education Studies, 2025)
This study investigated the impact of Virtual Reality (VR) technology on spatial intelligence development among elementary school students. A quasi-experimental pretest-posttest control group design was employed involving 120 fifth-grade students from two public schools in Jakarta, Indonesia. The experimental group (n=60) received VR-based spatial learning interventions for eight weeks, while the control group (n=60) received conventional instruction. Spatial intelligence was measured using adapted Spatial Ability Tests and Mental Rotation Tests. Data were analyzed using independent sample t-tests and ANCOVA (p<0.05). Results revealed that the VR experimental group demonstrated significantly higher spatial intelligence scores (M=78.45, SD=8.32) compared to the control group (M=65.23, SD=9.17) with t(118)=8.47, p<0.001, d=1.52. VR intervention showed substantial improvements in mental rotation ability (41.3% increase), spatial visualization (38.7% increase), and spatial orientation (35.2% increase). ANCOVA analysis confirmed significant VR effects on spatial intelligence (F(1,117)=72.34, p<0.001, partial η²=0.38). Additionally, 87% of experimental group students reported higher engagement levels. Virtual Reality technology significantly enhances spatial intelligence development in elementary students, offering superior outcomes compared to traditional methods. Integrating VR into elementary curricula represents an effective pedagogical strategy for developing spatial cognitive abilities.